Challenges of online education in rural Bangladesh during COVID-19 period: perceptions of higher secondary teachers and students - Islam, Md. Jubaydul (Brac University, 2021)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2021.